Compositional and diagenetic evolution of a siltstone, with implications for reservoir quality; an example from the Lower Triassic Montney Formation in western Canada. (July 2021) - Vaisblat, Noga; Harris, Nicholas B.; Ayranci, Korhan; Power, Matthew; DeBhur, Chris; Bish, David L.; Chalaturnyk, Rick; Krause, Federico; Crombez, Vincent; Euzen, Tristan; Rohais, Sebastien
Abstract: Diagenetic models for silt-rich mudstone (siltstone) are less advanced than those for sandstone and clay-rich mudstone. In addition, the influences of diagenetic processes on reservoir quality in siltstone formations are poorly understood. Here we examine the roles of depositional facies, detrital composition, and diagenetic processes in the compositional evolution and reservoir quality of the Lower Triassic Montney Formation, a prominent siltstone-dominated reservoir in western Canada with very large reserves of oil, gas-liquids and natural gas. We applied advanced, high-resolution petrographic methods including SEM (SE, BSE, EDX and SEM-CL), XRD, and QEMSCAN technologies, as well as He-pycnometry on samples from 17 different locations within the basin that represent a range of depths and thermal maturities. Cross-cutting and overgrowth relationships and volumes of authigenic phases demonstrate massive precipitation of quartz, feldspar, dolomite, calcite and anhydrite cements at shallow burial depths, leading to compositional homogeneity among different lithofacies. We propose that the precipitation of large volumes of cement resulted from high fluid flux through the formation at shallow depth, possibly driven by reflux of concentrated seawater in nearshore saltpans. Siltstones preserve relatively high porosity and permeability at shallow burial depths, differing from clay-rich mudstones. In contrast to sandstones, deep burial diagenesis played a relatively minor role in the compositional evolution of the Montney Formation siltstone and is expressed in the form of pressure solution and minor amounts of fibrous illite precipitation. Highlights: Diagenesis controls reservoir quality in the Montney Formation. Siltstones preserve higher porosity and permeability at shallow depth than shales. Extensive shallow burial diagenesis may be typical of siltstones. Diagenesis obliterated depositional influences on sediment composition.